National E-Governance Plan -Haryana: Successful Execution and Its Impact in State Reform: Streamlining administrative processes for effective governance in Haryana (Journal of Advances and Scholarly Researches in Allied Education, 2017)
Administrative process re-designing and change management in benefit conveyance offices like utilities, urban advancement, income, transport, social equity and strengthening, wellbeing, general wellbeing, business charges, Haryana urban improvement expert and Police division. The point is to dispose of superfluous advances and acquire objectivity basic leadership process. There is a requirement for re-composing of strategies in different zones of administrative movement and re-taking a gander at the exercises as such. The association of clients amid whole periods of venture life cycle, tending to issues looked by them and inspirations of workers at all levels is a basic achievement factor.